Solar still analyze with various water depth – a review (International Journal of Food and Nutritional Sciences, 2021)
Everyday people life water plays an critical role, due to population and industrialization drinking water is a rare one now a days. Solar desalination based thermal application is way to produce purify water in the world. Cords; stepped; wicks; absorber shapes; and rotating parts were used maintain minimum water depth of solar distiller